Kajian Desain dan Kinerja Jaringan Irigasi Mikro Berbasis Multi Komoditas di Sumedang - Wildan Herwindo; Aditya Prihantoko (Jurnal Irigasi, 2013)
Application of micro irrigation systems for high economic value crops can be an alternative to increase the efficiency of irrigation water use. This is caused that the implementation of micro irrigation using piping network in providing irrigation supply has very high efficiency, so it can optimize the use of water for irrigation and to support improving food security and water. This study aims to design a micro irrigation system design based multi-commodity and investigate the performance of its network. Method in this study is testing in the field using a physical model of micro irrigation located in Sumedang. Network-based multi-commodity micro irrigation applied using gravity water source that have 50 meters in difference. Based on the research results of the performance of the network obtained the average value of uniformity for micro irrigation in Sumedang, with drip emitters pipe is equal to 91.04%, while for micro sprayer emitters of 80.79%. In the application of micro irrigation network is note that the direction of the mounds on land with a rectangular shape should be parallel with the length of the land.